Stress Induced Deformation in Phyllite Rock in Mahadevtar Tunnel of KTFT Road Project - Sharma, Binayak; Acharya, Bimala; Shrestha, Bharat Lal; Paikara, Ramesh Kumar; Gautam, Niroj (KTFT Journal, 2024)
In the NATM Tunneling, the monitoring of the deformation of the surrounding rock is a basic means for confirmation consequently adaptation of the excavation stages as well as rock support measures. In the large tunnels, excavation and support works are carried out in different stages. Once the top heading portion of the tunnel was excavated, deformation leading to various types of problems on the primary support installed in the tunnel occurred at various spots in the approximately 329m stretch of the right tube and 182m stretch of the left tube in the Mahadevtar Tunnel of the Kathmandu Terai / Madhesh Fast Track (Expressway) Road Project (KTFT). Some of the problems noticed were longitudinal crack on shotcrete leading to spalling, steel ribs twisting, etc. The monitoring of the deformation was carried out and different correction measures were applied at site to ensure the long-term stability of the tunnel. For the sections yet to be excavated, the support measures were upgraded to cope with the encountered site situation. The numerical modeling was carried out considering original and modified rock support measures. The result showed that the support capacity curve for shotcrete is improved to a slight extent due to modified support measures. For the tunnelling in the weak rocks, selection of method and sequence of excavation, time taken between different stages of excavation and support application, adjustment of support measures as per site condition, and monitoring of the deformation are very crucial factors for the successful completion of the project. Monitoring of the deformation plays a crucial role to adjust support measures if required and to verify the adequacy of the installed support. Deformation shall be mostly converged, prior to installation of secondary support.